2010
DOI: 10.1097/bpo.0b013e3181df85ab
|View full text |Cite
|
Sign up to set email alerts
|

Results of Pavlik Harness Treatment in Children With Dislocated Hips Between the age of six and Twenty-four Months

Abstract: Therapeutic study, clinical case series: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 15 publications
2
39
0
5
Order By: Relevance
“…However, a recent retrospective study of the outcome of late-diagnosed DDH in infants who were treated with Pavlik harness beginning treatment at the age of 6-24 mo, showed encouraging results in the treatment of hip dislocation type Graf 3. Neither of the Graf 4 hips were successfully reduced [98] . Another study reported a successful treatment with Pavlik harness, in children aged 5 to 13 mo of age.…”
Section: The Pavlik Harnessmentioning
confidence: 99%
“…However, a recent retrospective study of the outcome of late-diagnosed DDH in infants who were treated with Pavlik harness beginning treatment at the age of 6-24 mo, showed encouraging results in the treatment of hip dislocation type Graf 3. Neither of the Graf 4 hips were successfully reduced [98] . Another study reported a successful treatment with Pavlik harness, in children aged 5 to 13 mo of age.…”
Section: The Pavlik Harnessmentioning
confidence: 99%
“…The switch from Pavlik to Camp within this time frame was supported by the thought that after stable reduction was managed using the Pavlik harness the residual dysplasia could now safely be treated with a more patient (parent) friendly abduction device. The prolonged use of the Pavlik harness was based on reports of successful reduction after the prolonged use of the Pavlik harness by van der Sluijs et al and Pollet et al [10, 13]. …”
Section: Methodsmentioning
confidence: 99%
“…Although late-diagnosed hip dislocations are now rarely seen because of national screening programmes, they still present a significant challenge in their management and literature supporting any treatment protocol remains scarce [2, 10]. In The Netherlands newborns at risk, or after a positive clinical examination, are to be screened with ultrasound at six–12 weeks as timely intervention can then be managed with a Pavlik harness, possibly followed by a Camp abduction brace if the result after Pavlik treatment is not satisfactory [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study was conducted by (Pollet et al, 2010) showed encouraging results with patients starting treatment at the age of 6-24 months of age.…”
Section: Introductionmentioning
confidence: 99%